Mucosal mast cell responses in rats (Rattus norvegicus) experimentally infected with Centrocestus caninus - Supap Saenphet (2018)
Mucosal mast cell (MMC) responses and worm recovery rates in rats experimentally infected with Centrocestus caninus were investigated. Metacercariae of C. caninus, procured from goldfish, Carassius auratus, were orally administered to twenty-five male rats (300 metacercariae each rat). The infected rats were sacrificed on days 3, 7, 14, 21 and 28 post-infection (Pl) along with the control rats. Worm recovery was performed from each part of small intestine. To investigate MMC, duodenal, jejunal and ileal paraffinized-tissue sections were processed and stained with 1% alcian blue and 0.5% safranin-O. The average worm recovery rates were 42.8, 37.7, 21.2, 12.5 and 3.7% on days 3, 7, 14, 21 and 28 PI, respectively. The majority of the worms (98.9%) were collected from the duodenum and jejunum. The MMC numbers in the infected rats were significantly higher than those of the controls (p<0.05). A peak level was observed on days 14 PI and the numbers gradually decreased thereafter. The results reveal that MMC plays an important role in the expulsion of C. caninus from the host intestine. A more precise description of the role the MMC plays in helminth expulsion is still needed to understand the mechanism of host defense against intestinal helminthic infection, along with other effector cells, such as goblet cells.